Pengaruh Variasi Produk dan Kemasan Terhadap Minat Beli Rokok Sampoerna (Studi Kasus Pada PT. Sampoerna, Tbk. Pagar Alam: Pengaruh Variasi Produk dan Kemasan Terhadap Minat Beli Rokok Sampoerna (Studi Kasus Pada PT. Sampoerna, Tbk. Pagar Alam (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
This study uses quantitative research in which there are two variables, namely product variation and packaging as independent variables and buying interest as dependent variables. By using data sources including: primary data, secondary data, population and sample. Data collection methods used were: observation, interview and questionnaire distribution to a number of respondents. By using a measure of validity and reliability, and using the analysis prerequisite test, then using data analysis methods using multiple regression analysis, correlation coefficient, coefficient of determination, hypothesis testing in the form of t test used to determine the extent to which the independent variables are used partially able to explain the dependent variable and the F test is used to determine the extent to which the independent variables used simultaneously are able to explain the dependent variable. Data analysis in this study used SPSS 23.0.From the results of this research, seen partially by t test that product variations influence the buying interest with tcount (8,839)> ttable (2,000), packaging influences the buying interest with tcount (12,040)> ttable (2,000) Furthermore, in the simultaneous influence test the F test shows that variations in products and packaging have a significant effect on buying interest, with Fcount (333,040)> Ftable (2.72). And the coefficient of determination shows that variations in changes in the variable purchase interest are influenced by changes in product and packaging variation variables by 89.6%. From the results of the study are expected to be beneficial to all parties.